Computer Aided Design of potential inhibitors for Gaucher disease - Noorbatcha, Ibrahim Ali; Mohd. Salleh, Hamzah (2010)
Acid β-glucosidase (GlcCerase) is a lysosomal enzyme, which is important in biodegradation of blood cells in human body. Mutation of GlcCerase will lead to Gaucher disease; the most common lysosomal storage disease. The current available treatments for Gaucher disease are enzyme replacement therapy and substrate reduction therapy; and both are costly. With the help of computer molecular modeling, new drug candidate for Gaucher disease treatment can be designed. In this research, we have successfully designed a lead-candidate to act as a potential inhibitor, as a part of substrate reduction therapy by adapting novel in silico method. Lamarckian genetic algorithm is used to locate the potential inhibitor sites in the acid β- glucosidase and strength of the binding is evaluated using potential mean force (PMF) scores. Good correlation between experimental inhibition constant (Ki) and computational binding score is established with the correlation coefficient of 0.782. This correlation used as to predict the unknown Ki value of the new ligand. N-decyl deoxynojirimycin gave a promising result to be considered as a candidate inhibitor.